Implementation of Modified MVC Model with Integrated Security in E-Procurement Application for Companies - Pratiwi, Ade (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This research discusses the implementation of a modified MVC (Model-View-Controller) model combined with advanced security features in an e-procurement application. The main objective of this study is to enhance both efficiency and security in the electronic procurement of goods and services. The proposed modification not only separates application logic, user interface, and database layers but also integrates critical security mechanisms, particularly in the areas of data validation, encryption, and user authentication. By applying these additional layers of protection, the system aims to minimise unauthorised access, prevent data breaches, and ensure the integrity of transactional information. The implementation results indicate that the developed e-procurement application is capable of accelerating transaction processes, maintaining data confidentiality, and significantly reducing the risk of system misuse or fraudulent activities. Furthermore, the approach supports compliance with best practices in secure software development. Therefore, the modified MVC model with integrated security features can be regarded as an effective and reliable solution to foster transparency, operational efficiency, and trustworthiness in modern electronic procurement systems.